2020
DOI: 10.3390/medicina56070355
|View full text |Cite
|
Sign up to set email alerts
|

A Patient with Cryoglobulinemic Membranoproliferative GN (MPGN) Who Survived COVID-19 Disease: Case Presentation and Current Data of COVID-19 Infection in Dialysis and Transplanted Patients in Greece

Abstract: The evolving pandemic of Coronavirus Disease 2019 has posed a substantial health risk worldwide. However, there is a paucity of data regarding the clinical course and the therapeutic management of patients with chronic kidney disease and COVID-19 infection. To date, most evidence has come from renal transplantation, with about 45 patients reported thus far, and the current data from the ERA-EDTA (ERACODA) registry for transplanted patients and patients on Renal Replacement Therapy (RRT); as for those with glom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Although the immunopathogenesis of these disorders is not fully understood, many researchers have observed a link between infections and the development of primary GN [27][28][29]. Moreover, in a cohort of 20 patients with primary GN, we previously showed that the frequencies of PD-1-positive and PD-L1-positive T and B lymphocytes were higher among patients suffering from PGN than in those diagnosed with NPGN or in the control group [30].…”
Section: Introductionmentioning
confidence: 89%
“…Although the immunopathogenesis of these disorders is not fully understood, many researchers have observed a link between infections and the development of primary GN [27][28][29]. Moreover, in a cohort of 20 patients with primary GN, we previously showed that the frequencies of PD-1-positive and PD-L1-positive T and B lymphocytes were higher among patients suffering from PGN than in those diagnosed with NPGN or in the control group [30].…”
Section: Introductionmentioning
confidence: 89%
“…The available literature described cases with underlying glomerular pathology exacerbated during SARS-CoV2 infection, e.g., IgA nephropathy [74], cryoglobulinemic MPGN [75], and Membranous nephropathy [76].…”
Section: Chronic Kidney Diseasementioning
confidence: 99%